Institutions Matter? - Przeworski, Adam (Government and opposition (London), 2004)
The main methodological problem in assessing the impact of political institutions on any kind of performance stems from the possibility that institutions may be endogenous. As a result, institutions cannot be matched for the conditions under which they function. Inferences from such non-experimental observations are subject to several biases and, in the end, our conclusions may not be robust. One should not be confident, therefore, that any institutions would function in the same way under conditions different from those from which they are transplanted.